Facile high yield synthesis of MgCo2O4 and investigation of its role as anode material for lithium ion batteries. Issue 12 (15th August 2019) - Kulkarni, Pranav; Ghosh, Debasis; Balakrishna, Geetha; Rawat, R.S.; Reddy, M.V.; Adams, Stefan
Abstract: In this article, we have reported a one-step scalable synthesis of MgCo2 O4 nanostructures as efficient anode material for Li-ion batteries and investigated the role of post-synthesis calcination temperature (400, 600 and 800 °C) on its physiochemical properties and electrochemical performances. The XRD pattern of the calcinated sample at 400 °C (MC 400) indicates a pure phase of MgCo2 O4 . However, on increasing the calcination temperature to 600 °C (MC 600), an additional phase corresponding to MgO was detected and the corresponding XRD peak intensity further increased on increasing the calcination temperature to 800 °C (MC 800 °C). This was accompanied by a morphological transformation from flake and rod-like nanostructures, to an agglomerated dense flake-like morphology. Electrochemical studies revealed that the calcination temperature plays an important role in determining the electrochemical performance of the MgCo2 O4 as anode material. In a half cell, the MC 600 showed the best electrochemical performance with high discharge capacity of 980 mA h g −1 (2nd discharge at 60 mA g −1 ) and a reversible discharge capacity of 886 mA h g −1 at the end of 50 cycles with high coulombic efficiency of 98%. Long term stability was carried out at 0.5C which showed a capacity retention of 358 mA h g −1 at the end of 500 cycles. The superior electrochemical performance of the MC600 can be attributed to the presence of the small amount of MgO, which is believed to provide the anode materials better structural stability during cycling. The claim was further supported by ex-situ TEM analysis of the anode material of a cycled cell (50 cycles). Graphical abstract: Image 1 Highlights: One-step scalable synthesis of MgCo2 O4 nanostructures Effect of calcination temperature on the electrochemical performance was studied Initial discharge capacity of 980 mAhg −1 with 90% capacity retention after 50 cycles Long term reversible capacity of 358 mAhg −1 was retained at 0.5C after 500 cycles Ex-situ TEM showed the structural stability of MC600 after 50 cycles